Microspheres for 3D bioprinting: a review of fabrication methods and applications - Karaman, Dmitri; Williams, Kira; Phelps, Jolene; La Boucan, Fynn; Lewandowski, Gretchen; O’Grady, Kerrin; Yu, Bosco; Willerth, Stephanie M. (Frontiers in Bioengineering and Biotechnology, 2025)
Bioprinting incorporates printable biomaterials into 3D printing to create intricate tissues that maintain a defined 3D structure while supporting the survival and function of relevant cell types. A major challenge in 3D bioprinting is tuning material properties to ensure compatibility with different types of cells, while accurately mimicking the physiological microenvironment. Developing novel bioinks tailored to specific applications can help address this challenge by combining various materials and additives to tune the bioink formulation. Microspheres - small spherical particles - can incorporate drugs or growth factors to enable their controlled release, encapsulate cells to provide protection during printing, and provide structural reinforcement to tune mechanical properties and enable complex architectures. The particles range in size from 1 to 1000 μm and can be tuned to meet desired functions by optimizing their mode of production and the materials used for fabrication. This review presents an overview of microsphere production methods and considerations for optimizing the production process. It then summarizes how microspheres have been used to date in bioprinting applications. Finally, the existing challenges associated with the creation and use of microspheres are discussed along with avenues for future research.